SUBTITLING STRATEGY IN QUESTION OF DIRECTIVE SPEECH ACT IN JOJO RABBIT MOVIE - Gina Shabrina; Agung Prasetyo Wibowo (UIN Raden Mas Said Surakarta, 2022)
Question of directive speech acts are frequently found in utterances of characters in many movies. There are so many movies that originate from overseas and undeniably in a different language from Indonesian, including English. Yet, not all Indonesians understand English, so it is important for it to have subtitles so Indonesian audience can understand the movie. To address this matter, this research analysed subtitling strategies that are used to translate question of directive speech acts in Jojo Rabbit movie using qualitative research by utilising Searle’s (1976) questions of directive speech acts theory and Gottlieb’s (1992) subtitling strategies. The data in this research is the English subtitle script and Indonesian subtitle of Jojo Rabbit movie. The aim of this research is to identify subtitling strategies that are used in question of Searle’s (1976) directive speech act in Indonesian subtitle translation by using Gottlieb’s (1992) theory in Jojo Rabbit movie. The results of this research showed that there are 130 questions of directive speech act in English and Indonesian subtitle of Jojo Rabbit movie, and 8 subtitling strategies that are used to translate directive speech acts question in the subtitle of this movie. These results also showed that the most dominant subtitling strategy for translating question of directive speech act in Jojo Rabbit movie is transfer.